2020
DOI: 10.1021/acsnano.9b08285
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic NQO1 Enzyme-Activated Near-Infrared Fluorescence Imaging and Photodynamic Therapy with Polymeric Vesicles

Abstract: The utilization of enzymes as a triggering module could endow responsive polymeric nanostructures with selectivity in a site-specific manner. On the basis of the fact that endogenous NAD­(P)­H:quinone oxidoreductase isozyme 1 (NQO1) is overexpressed in many types of tumors, we report on the fabrication of photosensitizer-conjugated polymeric vesicles, exhibiting synergistic NQO1-triggered turn-on of both near-infrared (NIR) fluorescence emission and a photodynamic therapy (PDT) module. For vesicles self-assemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(87 citation statements)
references
References 89 publications
0
87
0
Order By: Relevance
“…While many efforts are dedicated to sensing pH and hydrogen peroxide, many more biomedically relevant analytes may be measured, such as levels of ions, [63,[234][235][236][237] reactive oxygen or nitrogen species, [238][239][240][241][242][243][244][245][246] enzymes, [81,[247][248][249][250][251][252][253][254] glutathione, [255][256][257][258][259][260] and other biomarkers. [261][262][263] An example is the ratiometric hypochlorite sensor developed by Zou et al for the detection of arthritis ( Figure 11A).…”
Section: Sensing Other Biological Markersmentioning
confidence: 99%
“…While many efforts are dedicated to sensing pH and hydrogen peroxide, many more biomedically relevant analytes may be measured, such as levels of ions, [63,[234][235][236][237] reactive oxygen or nitrogen species, [238][239][240][241][242][243][244][245][246] enzymes, [81,[247][248][249][250][251][252][253][254] glutathione, [255][256][257][258][259][260] and other biomarkers. [261][262][263] An example is the ratiometric hypochlorite sensor developed by Zou et al for the detection of arthritis ( Figure 11A).…”
Section: Sensing Other Biological Markersmentioning
confidence: 99%
“…Without being triggered by NQO1, both fluorescence emission and photodynamic therapy (PDT) capability were turned off due to the “double quenching” effect. Upon cellular uptake, highly expressed NQO1 triggered the self-immolative cleavage of the quinone trimethyl lock, which then led to the release of photosensitizers, near infrared (NIR) emission and PDT activation, thereby realizing real-time monitoring and treatment of cancers [ 100 ].…”
Section: Stimulus-responsive Systemsmentioning
confidence: 99%
“…Numerous studies have shown that NQO1 is upregulated in breast cancer, pancreatic cancer, colorectal cancer, cervical cancer, and lung cancer (Ma et al, 2014 ; Yang et al, 2014 ). Yao et al ( 2020 ) reported that NQO1-responsive multifunctional polymer vesicles (named BCPs) covalently conjugated with PS (coumarin and Nile Blue). In the absence of NQO1, due to the “dual quenching” effect, that is to say, the quenching caused by aggregation caused by photoinduced electron transfer (PET) and the quenching of quinone production, the fluorescence emission and PDT efficiency were in the “off” state.…”
Section: Tmrns As Targeted Delivery Carriers For Photodynamic Anticanmentioning
confidence: 99%